Structural quality assessment of the villagemath instructional content platform - Joshua Abah ABAH (Journal of Advanced Sciences and Mathematics Education, 2024)
Background: The integration of culturally-based mathematics education is vital for making learning meaningful and relevant. The VillageMath platform was developed as a web-based ethnomathematics instructional content repository to address this need.Aims: This study aims to evaluate the structural quality of the VillageMath educational intervention, focusing on its navigation, structure, and appearance.Method: The study employed a developmental research design, involving 341 pre-service and in-service mathematics teachers in Benue State, Nigeria. The VillageMath platform was developed using WordPress Version 5.4, on a Linux OS server with cPanel v80.p (Build 20), Apache Version 2.4.39, PHP Version 5.6.40, and MySQL Version 5.7.26. The Web-based Ethnomathematics Instructional Content Repository Assessment Questionnaire (WEICRAQ) was used as the research instrument. Data were analyzed using mean and standard deviation to answer three research questions regarding the quality assessment of the web tool.Results: The analysis revealed that both pre-service and in-service mathematics teachers rated the VillageMath platform highly in terms of navigation, structure, and appearance.Conclusion: The findings indicate that VillageMath is a structurally sound platform that can be utilized by mathematics teacher educators in higher education institutions. The platform serves as a reliable tool for promoting narratives in ethnomathematics and provides a forum for experts to share and develop innovative pedagogical strategies, particularly those highlighting African indigenous knowledge systems.